Ultra rapid response to electroconvulsive therapy in a case of acute polymorphic psychotic disorder. - Quispe-Turpo, Fabiola (2019)
There is an erroneous perception that Electroconvulsive Therapy (ECT) should be used as a last resource of psychiatric management and only in chronic and refractory cases. This, among other causes, has led to an unfortunate decrement in its use during recent times both in our country and in other places. However, acute psychoses with catatoniform or motility symptoms have high favorable response rates, up to 100%, and ECT should, therefore, be a first line treatment resource for these disorders in order to prevent or avoid the occurrence of catatonia´s ominous consequences. The case of a patient with diagnosis of acute polymorphic psychotic disorder without symptoms of schizophrenia (F23.0, ICD-10) is presented. The patient achieved a complete remission of his catatonic and psychotic symptoms with a single session of ECT – an infrequent event by itself-. On this basis, e review of pertinent literature is conducted, and it is concluded that the ECT should resume its relevance in the management of acute cases with a good prognosis, as its postponement would bring up unnecessarily negative consequences.